Legal Power and Liability of Notary Towards The Content of Cover Note That is not Implemented In BTN Balikpapan - Hotma Elisa Irene Siahaan; Rasji, Rasji (Dinasti Research, 2024)
This article is titled Legal Power and Notary's Responsibility on the Content of Unexecuted Cover Note in BTN Balikpapan. Legal research method with Normative research type, using statute approach and conceptual approach as well as secondary data source which is using primary legal materials in the form of regulations relevant to legal issues, and secondary legal materials which are opinions and legal theories relevant to legal issues in this writing. So with this analysis, it is concluded that the cover note does not have absolute evidentiary power and only functions as additional evidence depending on the judge's judgment. The use of a cover note as the basis for the exercise of rights and obligations in a credit agreement is considered invalid because it cannot replace a notarial deed. The notary's responsibility related to the issuance of a cover note for bank credit disbursement is that the notary is fully responsible for the contents of the cover note he issued. If there is a discrepancy between the contents of the cover note and the actual conditions in the field, the notary must bear his responsibility, both administratively, criminally and civilly, and even morally.